2021
DOI: 10.1021/acs.jnatprod.0c01151
|View full text |Cite
|
Sign up to set email alerts
|

The Natural Alkaloid Berberine Can Reduce the Number of Pseudomonas aeruginosa Tolerant Cells

Abstract: The eradication of recurrent Pseudomonas aeruginosa (PA) lung infection in cystic fibrosis (CF) patients may be hampered by the development of persistent bacterial forms, which can tolerate antibiotics through efflux pump overexpression. After demonstrating the efflux pump inhibitory effect of the alkaloid berberine on the PA MexXY-OprM efflux pump, in this study, we tested its ability (80/320 μg/mL) to enhance tobramycin (20xMIC/1000xMIC) activity against PA planktonic/biofilm cultures. Preliminary investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 41 publications
1
26
0
Order By: Relevance
“…In this work, we evaluated the interaction between berberine and its three aromatic derivatives with the access to the periplasmic site between the periplasmic loop of TM7 and TM8 of the MexY protein, the inner transmembrane channel of the P. aeruginosa MexXY-OprM efflux pump, which is responsible for aminoglycoside extrusion. This site was selected because it is involved in the recruitment of lipophilic and small-sized substrates directly from the periplasmic space and it has been investigated in our previous research [11,12,41]. Indeed, a ligand that can bind strongly at this fissure could hamper the binding of natural substrates by hindering the conformational change in protomers in the MexY homotrimer in a non-competitive mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this work, we evaluated the interaction between berberine and its three aromatic derivatives with the access to the periplasmic site between the periplasmic loop of TM7 and TM8 of the MexY protein, the inner transmembrane channel of the P. aeruginosa MexXY-OprM efflux pump, which is responsible for aminoglycoside extrusion. This site was selected because it is involved in the recruitment of lipophilic and small-sized substrates directly from the periplasmic space and it has been investigated in our previous research [11,12,41]. Indeed, a ligand that can bind strongly at this fissure could hamper the binding of natural substrates by hindering the conformational change in protomers in the MexY homotrimer in a non-competitive mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, we optimized a full 3D model of the MexY structure using the highly similar models of the membrane channels P. aeruginosa MexB and Escherichia coli AcrB [9][10][11]. From a structural point of view, MexXY-OprM is a tripartite system characterized by a drug extrusion mechanism via a proton gradient as in all RND efflux systems [12]. MexY is the inner membrane protein, organized as a homotrimer presenting a transmembrane (TM) domain, with 12 alpha helices and a periplasmic domain, which is directly involved in the access, binding, and extrusion of substrates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is imperative to adopt effective measures to prevent biofilm propagation and control the associated infection successfully. Previous studies reported the inhibitory effects of BER against biofilm and MexXY-OprM efflux pump of clinical strains of Pseudomonas aeruginosa to some extent [47][48][49][50]; however, PAO1 is allowedly considered a model microorganism for biofilm research and the results obtained from this strain are more persuasive. In this study, sub-MIC doses of the BER-AZM combination treatment considerably inhibited the biomass, EPS, and total protein of PAO1 biofilm.…”
Section: Discussionmentioning
confidence: 99%
“…Berberine is the alkaloid present in the highest concentrations in the rhizomes of C. chinensis. It has antipathogen (Yan et al, 2008;Mangiaterra et al, 2021), antibacterial toxin, anti-inflammatory (Cuellar et al, 2001), hypoglycemic (Lee et al, 2006), anti-gastric ulcer, antitumor, and positive muscle strength effects and exerts a negative frequency on the myocardium. With further research, an increasing number of pharmacological effects induced by berberine have been discovered, and the corresponding mechanisms of action have also been explained.…”
Section: Introductionmentioning
confidence: 99%